Investigation of Dual-Vortical-Flow Hybrid Rocket Engine without Flame Holding Mechanism - A. Lai; T.-H. Chou; S.-S. Wei; J.-W. Lin; J.-S. Wu; Y.-S. Chen (International Journal of Aerospace Engineering)
A 250 kgf thrust hybrid rocket engine was designed, tested, and verified in this work. Due to the injection and flow pattern of this engine, this engine was named dual-vortical-flow engine. This propulsion system uses N2O as oxidizer and HDPE as fuel. This engine was numerically investigated using a CFD tool that can handle reacting flow with finite-rate chemistry and coupled with the real-fluid model. The engine was further verified via a hot-fire test for 12 s. The ground Isp of the engine was 232 s and 221 s for numerical and hot-fire tests, respectively. An oscillation frequency with an order of 100 Hz was observed in both numerical and hot-fire tests with less than 5% of pressure oscillation. Swirling pattern on the fuel surface was also observed in both numerical and hot-fire test, which proves that this swirling dual-vortical-flow engine works exactly as designed. The averaged regression rate of the fuel surface was found to be 0.6~0.8 mm/s at the surface of disk walls and 1.5~1.7 mm/s at the surface of central core of the fuel grain.